Sliding perspectives: dissociating ownership from self-location during full body illusions in virtual reality - Maselli, Antonella; Slater, Mel (Frontiers in Human Neuroscience, 2014)
Bodily illusions have been used to study bodily self-consciousness and disentangle its various components, among other the sense of ownership and self-location. Congruent multimodal correlations between the real body and a fake humanoid body can in fact trigger the illusion that the fake body is one’s own and/or disrupt the unity between the perceived self-location and the position of the physical body. However, the extent to which changes in self-location entail changes in ownership is still matter of debate. Here we address this problem with the support of immersive virtual reality. Congruent visuotactile stimulation was delivered on healthy participants to trigger full body illusions from different visual perspectives, each resulting in a different degree of overlap between real and virtual body. Changes in ownership and self-location were measured with novel self posture assessment tasks and with an adapted version of the cross-modal congruency task. We found that, despite their strong coupling, self-location and ownership can be selectively altered: self-location was affected when having a third person perspective over the virtual body, while ownership toward the virtual body was experienced only in the conditions with total or partial overlap. Thus, when the virtual body is seen in the far extra-personal space, changes in self-location were not coupled with changes in ownership. If a partial spatial overlap is present, ownership was instead typically experienced with a boosted change in the perceived self-location. We discussed results in the context of the current knowledge of the multisensory integration mechanisms contributing to self-body perception. We argue that changes in the perceived self-location are associated to the dynamical representation of peripersonal space encoded by visuotactile neurons. On the other hand, our results speak in favor of visuo-proprioceptive neuronal populations being a driving trigger in full body ownership illusions.